Improving Cognitive Performance of 9–12 Years Old Children: Just Dance? A Randomized Controlled Trial - van den Berg, Vera; Saliasi, Emi; de Groot, Renate H. M.; Chinapaw, Mai J. M.; Singh, Amika S. (Frontiers in Psychology, 2019)
Exercise is assumed to have positive effects on children’s cognitive performance. However, given the inconclusive evidence for the long-term effects of exercise, it is difficult to advice schools on what specific exercise programs can improve children’s cognitive performance. In particular, little is known about the effects of small exercise programs that may be feasible in daily school practice. Therefore, we assessed the effects of a 9-weeks program consisting of daily exercise breaks on children’s cognitive performance, aerobic fitness and physical activity levels. We conducted a cluster-randomized controlled trial in 21 classes of eight Dutch primary schools. A total of 512 children aged 9 – 12 years participated. The exercise intervention had a duration of 9 weeks and consisted of a daily 10-minute classroom-based exercise break of moderate to vigorous intensity. Before and after the intervention, we used four cognitive tasks (i.e. the Attention Network Test, Stroop test, d2 test of attention and Fluency task) to measure children’s cognitive performance in domains of selective attention, inhibition and memory retrieval. In addition, we measured aerobic fitness with a Shuttle Run test and physical activity during school hours by accelerometers. We analyzed data using mixed models, adjusting for baseline scores, class and school. After 9 weeks, there were no intervention effects on children’s cognitive performance or aerobic fitness. Children in the intervention group spent 2.9 minutes more of their school hours in moderate to vigorous physical activity as compared to the children in the control group. In conclusion, daily 10-minute exercise breaks in the classroom did not improve, nor deteriorate cognitive performance in children. The exercise breaks had no effect on children’s fitness, and resulted in 2.9 minutes more time spent in moderate to vigorous physical activity during school hours. Daily exercise breaks can be implemented in the classroom to promote children’s physical activity during school time, without adverse effect on their cognitive performance.